A Decomposition Analysis of Fertility: Evidence from DKI Jakarta and East Nusa Tenggara - Mangunsong, Farma (Economics and Finance in Indonesia, 2020)
Fertility control has been one of the priorities of development in Indonesia. However, the 2000 and 2010 population censuses showed an increase in fertility indicators. To identify the sources of increased fertility in developed and less developed areas, DKI Jakarta and East Nusa Tenggara Provinces were selected for comparison. Using 2000 and 2010 census data, the decomposition analysis shows that the increase in Total Fertility Rate (TFR) of DKI Jakarta was dominated by the increase in nuptiality rate, while the increase in TFR of East Nusa Tenggara was mainly caused by the increase in Marital Fertility Rate (MFR). The highest increase in the proportion of married women in DKI Jakarta occurs in the age group of 15-19 years old, followed by the age group of 20-24 years old. The increase in MFR in East Nusa Tenggara occurs in nearly all age groups, particularly in the age groups of 30-34 and 35-39 years old. Identifying theÂ sources of the increase in TFR is important for population policy to support population growth control, fertility reduction, and human resource quality improvement. The main suggestions based on the findings are the promotion of higher educational level and the benefits of postponing marriage among the younger age groups in DKI Jakarta as well as the use of contraceptive methods to control birth rate in East Nusa Tenggara.